The reshaping of Iran from Zoroastrian to Muslim a history of cultural transformation - Writer, Rashna (Lewiston : The Edwin Mellen Press, 2013)
The conquest of Sasanian Iran by the Arabs, newly galvanized by Islam, brought to a close Zoroastrian Iran which would henceforth become an integral part of the Islamic world. This book examines the transformation of the country and its impact on the diminished Zoroastrian community; and investigates Zoroastrian-Muslim relations in Iran, from the early post-conquest era to the present time.
Chapter Seven -- Shia Islam: Redefining a National IdentityChapter Eight -- Emasculation of the Zoroastrians in the Safavid Era; Chapter Nine -- The Qajar Dynasty: Further Denigration of the Zoroastrians; Chapter Ten -- The Pahlavi Dynasty: An Era of Religious Tolerance for the Zoroastrians; Chapter Eleven -- From Religious Tolerance to Islamic Revolution; CODA; Appendix; Bibliography; Index.
Description based on print version record.
Keywords: Islam -- Iran; Zoroastrianism; Religion and sociology; Political science; Economic history; Social history; POLITICAL SCIENCE / Public Policy / Cultural Policy; SOCIAL SCIENCE / Anthropology / Cultural; SOCIAL SCIENCE / Popular Culture; Electronic books